Modulatory Influence of Segmented Filamentous Bacteria on Transcriptomic Response of Gnotobiotic Mice Exposed to TCDD - Stedtfeld, Robert D.; Chai, Benli; Crawford, Robert B.; Stedtfeld, Tiffany M.; Williams, Maggie R.; Xiangwen, Shao; Kuwahara, Tomomi; Cole, James R.; Kaminski, Norbert E.; Tiedje, James M.; Hashsham, Syed A. (Frontiers in Microbiology, 2017)
Environmental toxicants such as 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), an aryl hydrocarbon receptor (AhR), are known to induce host toxicity and structural shifts in the gut microbiota. Key bacterial populations with similar or opposing functional responses to AhR ligand exposure may potentially help regulate expression of genes associated with immune dysfunction. To examine this question and the mechanisms for AhR ligand-induced bacterial shifts, C57BL/6 gnotobiotic mice were colonized with and without segmented filamentous bacteria (SFB)- an immune activator. Mice were also colonized with polysaccharide A producing Bacteroides fragilis-an immune suppressor to serve as a commensal background. Following colonization, mice were administered TCDD (30 µg/kg) every 4 days for 28 days by oral gavage. Quantified with the nCounter® mouse immunology panel, opposing responses in ileal gene expression (e.g., genes associated with T-cell differentiation via the class II major histocompatibility complex-MHC II) as a result of TCDD dosing and SFB colonization were observed. Genes that responded to TCDD in the presence of SFB did not show a significant response in the absence of SFB, and vice-versa. Regulatory T-cells, examined in the mesenteric lymph-nodes, spleen, and blood were also less impacted by TCDD in mice colonized with SFB. TCDD-induced shifts in abundance of SFB and B. fragilis compared with previous studies in mice with a traditional gut microbiome. With regard to the mouse model colonized with individual populations, results indicate that TCDD-induced host response was significantly modulated by the presence of SFB in the gut microbiome, providing insight into therapeutic potential between AhR ligands and key commensals.